Bird response to intercropping switchgrass within a loblolly pine plantation - Craig Marshall; Samuel K. Riffell; Darren A. Miller; JoVonn G. Hill; Kristine O. Evans; Scott A. Rush (Wildlife Society Bulletin)
ABSTRACT Global interest in alternative, renewable energy sources has led to the development of novel land‐use practices and techniques aimed at maximizing energy production while also minimizing environmental, economic, and societal costs. One such novel practice is intercropping switchgrass (Panicum virgatum) within loblolly pine (Pinus taeda) plantations. However, minimal knowledge currently exists regarding the influence of intercropping switchgrass on ecosystem functions and services and biological diversity of loblolly pine plantations. Therefore, we assessed the influence of intercropping switchgrass on breeding‐bird species density and community composition during 2014–2015 in Mississippi, USA. We had 3,619 detections encompassing 39 species, with 10 species used in density analysis. Breeding‐bird density estimates did not significantly differ for 8 out the 10 species modeled between control and intercrop treatments. However, white‐eyed vireo (Vireo griseus) and indigo bunting (Passerina cyanea) densities differed between intercrop and control, with white‐eyed vireos having a greater density on control and indigo buntings having a greater density on intercrop. Treatment influenced breeding‐bird community composition, with monocultures supporting an atypical species composition within a loblolly pine plantation, but species composition did not differ between control and intercrop treatments. © 2017 The Wildlife Society.